Synergistic antitumor activity by combining trastuzumab with retinoic acid in HER2 positive human breast cancer cells - Vanderhoeven, Fiorella (Oncotarget, 2018)
Breast cancer can be classified into molecular subtypes. Tumors overexpressing HER2 protein are more aggressive and metastatic; hence, patients have a poor prognosis. Anti-HER2 strategies, such as the monoclonal antibody Trastuzumab (Tz), have therefore been developed. Despite this progress, not all patients respond to the treatment. Retinoic acid (RA) has been proposed as an adjuvant treatment of breast carcinoma because of its ability to inhibit cell growth. We evaluated the effect of Tz in combination with RA on the viability, adhesion, migration, invasion and expression of migration-related proteins in SKBR3 and BT-474 human breast cancer cells. MTT, pharmacological interaction analysis, immunofluorescence, adhesion/migration/invasion and Western blot assays were performed. The coadministration of both drugs synergistically decreased cell survival. Tz+RA significantly decreased adhesion/migration/invasion in both cell types. Tz+RA strongly reduced FAK and HER2 expression and induced nuclear FAK translocation. In addition, a granular distribution of HER2 receptor was observed after the combined treatment. In conclusion, the coadministration of both drugs in patients with this type of cancer could contribute to the improvement of their prognosis and reduce the adverse effects of therapy because the applied Tz doses would be lower due to the adjuvant effect of RA.